MECHANICAL PROPERTIES OF Cu SURFACE IN THE LAMINATED STRUCTURE OF Cr-Cu COATINGS - Tri Widodo Besar Riyadi (Media Mesin: Majalah Teknik Mesin, 2017)
A laminated structure of Cr-Cu coating was produced by electroplating on a carbon steel substrate. Two baths of chromium and copper electrolyte solutions were prepared to respectively deposit Cr and Cu as the first and second layer. The Cr was plated using the same plating time of 60 minutes, whereas Cu was deposit using plating time of 1 hour, 1.5 hours, 2 hours, 3 hours and 3.5 hours. The effect of plating time on the thickness, hardness and specific wear rate of the Cu surface was investigated. The formed phase, thickness, hardness and specific wear rate of the Cu surface were observed using XRD, optical microscope, Vickers microhardness tester and Ogoshi wear rate tester, respectively. The results show that Cu was formed on the surface. An increase of the Cu plating time increased the thickness and the specific wear rate of the Cu surface, but reduced the hardness of Cu surface. Cu layer was observed denser than that of Cr. This study showed that the use of Cu can be a potential candidate to laminate Cr for use in corrosive environment.  Keywords